Analisis Penilaian Berbasis Fortofolio pada Pembelajaran Tematik Kelas 3 di Sekolah Dasar Negeri Batujaya Kecamatan Batu Ceper - Magdalena, Ina; Ramdhan, Savina Nurrahmadanti; Luftiyah, Vivi (Lembaga Yasin AlSys, 2021)
This research was conducted to describe the Analysis of Fortofolio Based Assessment in Grade 3 Thematic Learning as an assessment and evaluation tool for the learning process of students. One of the advantages of portfolio assessment is that it provides opportunities for students to be more involved, and students themselves can more easily control the extent to which the development of abilities they acquire. In the world of education, teachers can use portfolios to see the progress of students from time to time based on a collection of work as evidence of a learning activity. This Portfolio Assessment was carried out using a descriptive method to obtain a detailed description of the portfolio-based assessment. Data collection techniques used are documentary studies, observations and interviews. The research subjects were principals, teachers and students. The research data reveals that a portfolio-based assessment on thematic learning has been carried out in one of the SD Negeri Batu Jaya, Batu Ceper District. The results showed that the planning stage had been prepared by the teacher since the beginning of the thematic learning stage. Implementation of the assessment makes teachers improve their professionalism in compiling and recording student learning achievements. Portfolio assessment reporting enables learners to be more active and creative in assigned work. The obstacle encountered was the difficulty of teachers in managing the portfolio assessment process sequentially, due to a lack of understanding of the practicality of portfolio assessment. In conclusion, the application of portfolio assessment to thematic learning provides a change in the way teachers record student achievement, and allows them to increase their creativity in giving assignments.